Insect Antimicrobial Peptides: Advancements, Enhancements and New Challenges - Matteo Dho; Valentina Candian; Rosemarie Tedeschi (MDPI AG, 2023)
Several insects are known as vectors of a wide range of animal and human pathogens causing various diseases. However, they are also a source of different substances, such as the Antimicrobial Peptides (AMPs), which can be employed in the development of natural bioactive compounds for medical, veterinary and agricultural applications. It is well known that AMP activity, in contrast to most classical antibiotics, does not lead to the development of natural bacterial resistance, or at least the frequency of resistance is considered to be low. Therefore, there is a strong interest in assessing the efficacy of the various peptides known to date, identifying new compounds and evaluating possible solutions in order to increase their production. Moreover, implementing AMP modulation in insect rearing could preserve insect health in large-scale production. This review describes the current knowledge on insect AMPs, presenting the validated ones for the different insect orders. A brief description of their mechanism of action is reported with focus on proposed applications. The possible effects of insect diet on AMP translation and synthesis have been discussed.